1999
DOI: 10.1093/jnci/91.17.1475
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk After Bilateral Prophylactic Oophorectomy in BRCA1 Mutation Carriers

Abstract: Bilateral prophylactic oophorectomy is associated with a reduced breast cancer risk in women who carry a BRCA1 mutation. The likely mechanism is reduction of ovarian hormone exposure. These findings have implications for the management of breast cancer risk in women who carry BRCA1 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
295
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 612 publications
(309 citation statements)
references
References 13 publications
8
295
0
6
Order By: Relevance
“…33 Currently, nonsurgical chemoprevention options available for BRCA carriers are based on interrupting the estrogen-signalling pathway and implicate an important role of sex hormones in the etiology of the disease. Although the majority of BRCA1 (but not BRCA2) tumours are estrogen receptor negative, oophorectomy [34][35][36] and tamoxifen 37 have been shown to reduce the risk of breast cancer among carriers of either mutation. Based on this observation, alternative dietary and lifestyle strategies that minimize exposure to estrogen or alter the 2-OHE/16a-OHE ratio may also impact overall risk.…”
Section: Discussionmentioning
confidence: 99%
“…33 Currently, nonsurgical chemoprevention options available for BRCA carriers are based on interrupting the estrogen-signalling pathway and implicate an important role of sex hormones in the etiology of the disease. Although the majority of BRCA1 (but not BRCA2) tumours are estrogen receptor negative, oophorectomy [34][35][36] and tamoxifen 37 have been shown to reduce the risk of breast cancer among carriers of either mutation. Based on this observation, alternative dietary and lifestyle strategies that minimize exposure to estrogen or alter the 2-OHE/16a-OHE ratio may also impact overall risk.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have reported that prophylactic oophorectomy reduced the risk of developing breast cancer in BRCA1-mutation carriers by 50%. 102 However, the benefit of tamoxifen remains controversial. The protective effect of tamoxifen against breast cancer has been demonstrated in women with moderate risk factors, but the data specific for carriers of BRCA1 mutations remain unclear.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Identification of these individuals before they present with cancer is important since prophylactic surgery can reduce morbidity and mortality in these individuals (Struewing et al, 1995;Rebbeck et al, 1999;Hartmann et al, 1999;Hartmann et al, 2001;Meijers-Heijboer et al, 2001;Kauff et al, 2002;Rebbeck et al, 2004). Unfortunately, genetic testing is expensive, family history of breast cancer is common and BRCA mutations are rare (Ford et al, 1994;Peto et al, 1999;Antoniou et al, 2002).…”
mentioning
confidence: 99%